The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1080/21691401.2021.1903478
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of silver nanoparticles using Ziziphus nummularia leaf extract and evaluation of their antimicrobial, antioxidant, cytotoxic and genotoxic potential (4-in-1 system)

Abstract: This study reports the synthesis of silver nanoparticles (AgNPs) from silver nitrate by leaf extract of a medicinal plant Ziziphus nummularia. The leaf extract acts as a reducing and stabilizing agent for the formation of nanoparticles. The green synthesized AgNPs were characterized by ultraviolet-visible (UV-vis) spectroscopy, Fourier transform infrared (FITR) spectroscopy, Thermogravimetric analysis (TGA), X-ray diffraction (XRD), transmission electron microscopy (TEM) analysis and evaluated their antimicrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
(36 reference statements)
3
10
0
Order By: Relevance
“…These silver nanoparticles exhibited efficient anti-microbial commotion against S. aureus, C. rubrum, S. typhimurium, P. aeruginosa, C. neoformans, C. albicans, and C. glabrata. Silver nanoparticles also exhibited good DPPH activity (IC 50 = 520 mg/mL) and ABTS activity (IC 50 = 55 mg/mL) [201]. A previous study confirmed for first time the capability of Otostegia persica for the bio-synthesis of silver nanoparticles.…”
Section: Synthesis Of Silver Nanoparticles Using Leaf Extracts: (2019-2020)mentioning
confidence: 52%
“…These silver nanoparticles exhibited efficient anti-microbial commotion against S. aureus, C. rubrum, S. typhimurium, P. aeruginosa, C. neoformans, C. albicans, and C. glabrata. Silver nanoparticles also exhibited good DPPH activity (IC 50 = 520 mg/mL) and ABTS activity (IC 50 = 55 mg/mL) [201]. A previous study confirmed for first time the capability of Otostegia persica for the bio-synthesis of silver nanoparticles.…”
Section: Synthesis Of Silver Nanoparticles Using Leaf Extracts: (2019-2020)mentioning
confidence: 52%
“…Song et al [219] prepared multifunctional silver-embedded magnetic NPs; the silicaencapsulated magnetic NPs produce surface-enhanced solid Raman scattering signals to target breast cancer cells and floating leukemia cells [220]. A study showed developed carrier molecules such as chitosan to deliver silver to the cancer cells rather than using AgNPs directly.…”
Section: Anticancer Activity Of Agnpsmentioning
confidence: 99%
“…This increases the potential activity of the nanoparticles. [97]; Padalia, H. and Chanda, S., 2021 [98]; Padalia, H. and Chanda, S., 2021 [96], Khan et al, 2016 [94]; Parmar and Jangir, 2017 [95].…”
Section: Other Activitiesmentioning
confidence: 98%
“…Not only has green synthesis given more stable nanoparticles compared to other methods, but also it has been scalable and eco-friendly without any requirement for high temperatures and pressure or the use of toxic chemicals. So far, Ziziphus nummularia leaf extracts have been used in the green synthesis of silver [6,[94][95][96], gold [95], and zinc nanoparticles [97] (Figure 3). Indeed, during the formation of nanoparticles, the extract of Z. nummalaria functions as a reducing and stabilizing agent [96].…”
Section: Other Activitiesmentioning
confidence: 99%
See 1 more Smart Citation